Avaliação da política de ressocialização do preso no Ceará: a remição da pena pelo incentivo à leitura - Dumont, Felipe Vieira Rodrigues (2020)
The central idea of this study is to evaluate and understand the prisoner's re-socialization policy in Ceará, based on the teachers' perception. To this end, we will evaluate the remission project by encouraging reading in Ceará, which is the general objective of the research. As a specific objective, we have to understand the meaning of resocialization through reading for the subjects involved in the implementation of this policy, in this case, the teachers of the Livro Aberto project, as well as to verify the extent to which access to education, culture and capacity development criticism of the detainees had been reached. Initially, we made a historical and sociological rescue of the resocializing character attributed to punishment as a way of understanding the centrality of resocialization in the official discourse. We discussed the content given to the concept of resocialization, building substrate to perceive its weaknesses and potentialities, making an articulation with the investigated resocialization project. This evaluative research is fundamentally qualitative, using a case study in order to obtain data and understand the complexity of the investigated phenomenon. During the course of the research, we used both bibliographic data, as well as official project documents and reports for an in-depth analysis of the policy. As a data collection technique, we conduct interviews with teachers. We detected a limited performance of reading as a policy of re-socialization. This is due to the conditions in the prisons, the lack of commitment of the security agents. But also because of the utilitarian vision of the resocialization institute.